Nesting Ecology of the Painted Stork Mycteria leucocephala at Koonthankulam Birds Sanctuary, Tirunelveli, Tamil Nadu - Ramarajan, Sekar; Kumar, Pandian; Edison, S. Darwin Paul (Indian Forester, 2021)
Koothankulam bird sanctuary, in Tamil Nadu, India is an important site for about 117 wetland (migratory/residential) birds that visit migratory every year. Painted stork nesting habit and habitat was observed during the field survey carried out in October 2018 to May 2019. Painted stork is Residential migrant, near threatened as per IUCN, wildlife protection act 1972 and also prominent colonial nester of the heronries in this sanctuary. Nests were found even in densely populated areas, frequently close to pond center and edge of pond. Nest-building began in mid- December, immediately after the monsoon. Egg-laying began in the early January, with most chicks hatching by mid-February and fledging by mid-March. To address these issues, authors observed reproductive output, nesting tree characteristics, nest dimension, part of used plant materials and factors associated with yearly variation in nesting densities of the Painted stork at sanctuary. The sanctuary along with associated wetlands is important for the long-term monitoring of Painted stork and other water birds in nesting ecology for their conservation of near threatened.